The Opening And Closing Of The Doors Of The Skies: An Analytical Study From The Perspective Of The Quran And Sunnah - Mesbahul Hoque; Norhasnira Ibrahim; Mohd Zohdi Mohd Amin; Kauthar Abd Kadir (Usuli Faqih Research Centre PLT., 2025)
Index Publication (Tier 3)